2021
DOI: 10.1186/s12862-021-01777-x
|View full text |Cite
|
Sign up to set email alerts
|

The iron-sulfur scaffold protein HCF101 unveils the complexity of organellar evolution in SAR, Haptista and Cryptista

Abstract: Background Nbp35-like proteins (Nbp35, Cfd1, HCF101, Ind1, and AbpC) are P-loop NTPases that serve as components of iron-sulfur cluster (FeS) assembly machineries. In eukaryotes, Ind1 is present in mitochondria, and its function is associated with the assembly of FeS clusters in subunits of respiratory Complex I, Nbp35 and Cfd1 are the components of the cytosolic FeS assembly (CIA) pathway, and HCF101 is involved in FeS assembly of photosystem I in plastids of plants (chHCF101). The AbpC protei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 103 publications
(138 reference statements)
1
6
0
Order By: Relevance
“…Another clue of evolutionary specialization comes from the different localization of protein isoforms in different species, hinting for a possible association to different Fe-S cluster biogenesis machineries. While HCF101 was initially characterized as a chloroplast-associated protein with a specialized function in maintaining PSI homeostasis, a recent study suggested a wider diversity in localization for HCF101 paralogs across eukaryotes, especially in alveolates, with isoforms potentially localizing to the mitochondrion in Tetrahymena or in the cytosol in T. gondii [23]. Our study confirms that although T. gondii harbors a plastid, TgHCF101 is expressed in the cytosol (Fig.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Another clue of evolutionary specialization comes from the different localization of protein isoforms in different species, hinting for a possible association to different Fe-S cluster biogenesis machineries. While HCF101 was initially characterized as a chloroplast-associated protein with a specialized function in maintaining PSI homeostasis, a recent study suggested a wider diversity in localization for HCF101 paralogs across eukaryotes, especially in alveolates, with isoforms potentially localizing to the mitochondrion in Tetrahymena or in the cytosol in T. gondii [23]. Our study confirms that although T. gondii harbors a plastid, TgHCF101 is expressed in the cytosol (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…We performed homology searches in the http://www.ToxoDB.org database to retrieve members of the Mrp/NPB35 family encoded by the T. gondii genome. Besides TgNBP35, that has an unusual mitochondrial localization in T. gondii [20,23], we identified TGGT1_318590 as a potential homologue of HCF101. A broader phylogenetic analysis that included members of the Mrp/NPB35 family from a wide variety of eukaryotes (Table S1), revealed that this putative T. gondii homologue clearly segregates with members of the HCF101 group (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the cytosolic scaffold NBP35, which plays a central role in assembling cytosolic clusters, was found to be bound to the outer surface of the mitochondria (23), whereas in other model systems it is a soluble cytosolic protein, with one study suggesting a nuclear localisation (50). The exact reason for NBP35's re-localisation remains unclear, but it may highlight the connection between the CIA and ISC pathways in apicomplexan parasites and reflects the complex evolutionary history of these proteins in eukaryotes (51)(52)(53) Studies in a wide array of organisms clearly show that the role of the ABCB7 transporter in connecting the mitochondrial ISC and cytosolic CIA pathway is conserved (3). Downstream cytosolic Fe-S proteins are dependent on the cysteine desulfurase activity of the mitochondrial NFS1 enzymes, and the resulting sulfur intermediate that is transported out of the mitochondrial matrix by ABCB7.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the cytosolic scaffold NBP35, which plays a central role in assembling cytosolic clusters, was found to be bound to the outer surface of the mitochondria (23), whereas in other model systems it is a soluble cytosolic protein, with one study suggesting a nuclear localisation (50). The exact reason for NBP35’s re-localisation remains unclear, but it may highlight the connection between the CIA and ISC pathways in apicomplexan parasites and reflects the complex evolutionary history of these proteins in eukaryotes (5153)…”
Section: Discussionmentioning
confidence: 99%